Arginine 485 of human serum albumin interacts with the benzophenone moiety of ketoprofen in the binding pocket of subdomain III A and III B - Kaneko, K.; Chuang, Victor; Ito, T.; Suenaga, A.; Watanabe, H.; Maruyama, T.; Otagiri, M. (Govi Verlag Pharmazeutischer Verlag GmbH, 2012)
Arylpropionic acid nonsteroidal anti-inflammatory drusg (NSAIDs) primarily bind to subdomain III A (site II) of human serum albumin (HSA). Ketoprofen (KP), an arylpropionic acid that contains a photoreactive benzophenone moiety, was used to photolabel the binding region of site II. LC/Q-TOF mass spectrometry determination revealed that R485 was the amino acid residue that formed covalent adduct with the benzophenone moiety of KP. Point mutation of arginine 485 to alanine showed a slight decrease in the overall binding percentage of KP when compared to that of native HSA. The induced circular dichroism spectral data of KP with both R485A and native albumin confirmed the photolabeling findings. Interestingly, an increase in the extent of [14C]KP covalent adduct formation with the 11.6 kDa peptide derived from subdomain IIB-IIIA was observed for R485A. In contrast, mutation of arginine 410 caused a significant reduction of binding percentage, confirming the importance of this residue in high affinity binding of arylpropionic acid derivatives. This may indicate that while KP's carboxylate interacts electrostatically with arginine 410, the benzophenone moiety may have swung away from helix 6 in the absence of arginine 485. In this study, photolabeling of native and mutants albumins, R485A and R410C with [14C]KP confirmed that R485 involved in the non-electrostatic interaction with the benzophenone moiety of KP, but not vital to hold KP in the binding pocket of subdomain IIIA.